The value of the autopsy in clinical medicine - Innes, David Findlay (University of Cape Town, 2017)
The main purpose of this study was to assess the value of the autopsy in clinical medicine today. This has been achieved by analysing several variables. Clinical diagnostic accuracy was determined by assessing the concordance/discrepancy of clinical and autopsy diagnoses. In addition, several variables were assessed, namely whether or not the size of the hospital, type of ward, autopsy rate, age of the patient, and degree of confidence with which the clinical diagnosis was made had any bearing on the accuracy of the diagnosis. The impact of the newer diagnostic tests on clinical diagnosis was also assessed to confirm or refute the widely held opinion amongst clinicians that diagnostic advances have indeed reduced the need for autopsies. The attitudes of pathology registrars and consultants towards the autopsy were analysed, using a questionnaire proposed by Stubbs et al.